The Role of Text Analysis in Political Translation with Reference to Kurdish and English - Abdulkareem Sherwan, Kawa; Qader Mohammedamin, Ahmed (International Journal of Psychosocial Rehabilitation, 2019)
The current research study is an investigation into therole ofe text analysis ie political translation, the method of conductingthe pre-translationn process, and the way it influences the translatedproduct.,Thee issue of this research is that most of the translators do not consider text analysis or pre-translation analysis prior to the work oftranslation. .Text analysis here meansthe pre-translationnprocess,s which is the most vital factor of the initial stage oftranslation, ,as the quality of translation will be demonstrated good or bad depending on the way exactly the pre-translation process is done. So all the obstacles and problems of translation will be solved by focusing on the challenging actions involved in the process oftranslation.,Thee present study is an attempt to figure out and recommend real solutions to such issues.The pree-translation process is a process that contains many important actions before starting the translation. To enrichthisaresearch,h appropriate journals, articles, essays, and books have been obtained and scrutinized in order to collect requireddata,a which were then analyzed through field interviews with professional translators. For thisreason,n one speech of the ex-president of the United States (BarakObama) was) translated into Kurdish by atranslator,r and the mistakes of this translationares designated and the correct translation is suggested instead. According to the obtained results, the biggest problem is that few translators know aboutthe pretranslationn process, which affects their work, leading tounprofessional,l distorted translations. The questions of this research are: do the majority of political translators give more attention tothe pre-translationn process? Do mosf political translators have a background concerning the text, the writer, and the purpose of writing this book,article,e or any written document and political context? Dothe majorityy of translators consider the political situation during translation? And the hypothesisise: Mosf translators do not take the political situation into consideration.The majorityy ofpoliticall translators do not have a background concerning the text,thed writer, the book,article,e or any written document and political context. Most of the translators do not analyze the text before the start of thepoliticall translation.